Application of multi-valued weighting logical functions in the analysis of a degree of importance of construction parameters on the example of hydraulic valves - Deptuła, Adam (Zielona Góra: Uniwersytet Zielonogórski)
In the optimization process, changes in the construction parameters value influence the behaviour of functions depending on time. Weighting logical coefficients for the stabilisation time are taken into consideration here, i.e., a shorter (better) stabilisation time has a more important (bigger) value of the weighting coefficient. An example of applying weighting logical functions in the analysis of a degree of importance of construction parameters of a hydraulic valve is presented in the paper.
Keywords: optimization process; weighting logical coefficients; hydraulic valves; pomps